PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA LS Cafe RESTO KOTA BENGKULU - Ratnawili Ratnawili; Ledi Saputra (Yayasan Insani Mandiri Santani, 2023)
This research was conducted at LS Cafe Resto Bengkulu City, with the formulation of the problem: Does Leadership Style, Compensation and Work Environment affect employee performance and the number of respondents in this study were 42 respondents using total sampling. Based on the results of research that has been done about the influence of Leadership Style (X_1), Compensation (X2), and Work Environment (X3) on Employee Performance (Y) At LS Cafe Resto Bengkulu City, it can be concluded as follows: Leadership Style has an effect on Employee Performance in LS Cafe Resto Bengkulu City, this is evidenced by the results of the t test showing the value of t_hit>t_(α/2) (3.906 > 2.021) and (sig = 0.000 < 0.050). This means that H_0 is rejected and H_a is accepted. This is due to the workload carried out by nurses who have multiple roles. Compensation has a significant effect on employee performance at LS Cafe Resto Bengkulu City, this is evidenced by the results of the t test showing the value of t_hit>t_(α/2) (2,961 > 2.021) and (sig á = 0.000 < 0.050). This means that H_0 is rejected and H_a is accepted. Work environment has a significant effect on employee performance at LS Cafe Resto Bengkulu City, this is evidenced by the results of the t test showing the value of t_hit>t_(α/2) (6.785 > 2.021) and (sig = 0.000 < 0.050). This means that H_0 is rejected and H_a is accepted. Leadership Style (X_1), Compensation (X2), and Work Environment (X3) together have an effect on Employee Performance (Y) at LS Cafe Resto Bengkulu City, this is evidenced by the F test showing the value F_count>F_table, namely ( 74.424 > 4.072) and (sig = 0.000 < 0.05). This means that H_0 is rejected and H_a is accepted. Keywords: Leadership Style, Compensation, Work Environment Employee Performance